Expansion Hamiltonian model for a diatomic molecule adsorbed on a surface: vibrational states of the CO/Cu(100) system including surface vibrations - Meng, Qingyong; Meyer, Hans-Dieter (The journal of chemical physics, 2015)
Molecular-surface studies are often done by assuming a corrugated, static (i.e., rigid) surface. To be able to investigate the effects that vibrations of surface atoms may have on spectra and cross sections, an expansion Hamiltonian model is proposed on the basis of the recently reported [R. Marquardt et al., J. Chem. Phys. 132, 074108 (2010)] SAP potential energy surface (PES), which was built for the CO/Cu(100) system with a rigid surface. In contrast to other molecule-surface coupling models, such as the modified surface oscillator model, the coupling between the adsorbed molecule and the surface atoms is already included in the present expansion SAP-PES model, in which a Taylor expansion around the equilibrium positions of the surface atoms is performed. To test the quality of the Taylor expansion, a direct model, that is avoiding the expansion, is also studied. The latter, however, requests that there is only one movable surface atom included. On the basis of the present expansion and direct models, the effects of a moving top copper atom (the one to which CO is bound) on the energy levels of a bound CO/Cu(100) system are studied. For this purpose, the multiconfiguration time-dependent Hartree calculations are carried out to obtain the vibrational fundamentals and overtones of the CO/Cu(100) system including a movable top copper atom. In order to interpret the results, a simple model consisting of two coupled harmonic oscillators is introduced. From these calculations, the vibrational levels of the CO/Cu(100) system as function of the frequency of the top copper atom are discussed.
Gesehen am 12.06.2020